Short communication: Diversity of cave-dwelling bats in Cebu Island, Philippines - STEVE MICHAEL T. ALCAZAR; Ireneo L. Lit; Carmelita M. Rebancos; Aimee Lynn B. Dupo; Anna Pauline O. De Guia; Nathaniel C. Bantayan; JAMES DV. ALVAREZ (Biodiversitas Journal of Biological Diversity, 2020)
Abstract. Alcazar SMT, Lit Jr IL, Rebancos CM, Barrion-Dupo ALA, De Guia APO, Bantayan NC, Alvarez JDV. 2020. Short communication: Diversity of cave-dwelling bats in Cebu Island, Philippines. Biodiversitas 21: 3249-3254. The species composition and richness of cave-dwelling bats in 16 caves of Cebu Island were studied to provide resource managers and local government units in Cebu baseline information that may be used toward conservation and sustainable utilization and management of local cave resources. Stationary and mobile mist-netting were employed at the entrance and dark zones of the caves to maximize the capture of bats. The study accounts for 15 species of cave bats, of which two were unidentified but are believed to be potentially new species, namely Rhinolophus sp. and Myotis sp., and three are new distribution records to Cebu, namely Rhinolophus philippinensis, Eonycteris robusta, and Megaderma spasma. In terms of richness values, Balay’g Agta holds six species and the remaining caves have less than five species. The presence of endemic, potentially new species and new distribution records of bats presents high conservation value and raises concern and calls for urgent action to protect the caves and the resources therein.